INTERNET OF THINGS FOR ROBOTIC PROJECTS - Igor Nevliudov; Oleksandr Tsymbal; Artem Bronnikov; Olexandr Mordyk (Сучасний стан наукових досліджень та технологій в промисловості, 2020)
The subject of research in the article is the application of IOT technology in flexible integrated robotic systems. The goal of the work is to integrate IOT technology with models and decision-making methods in order to create an adaptive control system for flexible robotic production. The article solves the following tasks: to analyze the application of IOT technologies in various fields, including in robotics, to consider the construction of an intelligent decision-making system as one of the key elements of automated control systems, to consider the development of an adaptive control system for a flexible robotic section and its individual modules. The following results were obtained: the main features of the IOT technology were analyzed, including those for implementation in flexible integrated systems of modern production; it is proposed to introduce intelligent production agents into the composition of technological systems, as means of transport and auxiliary assembly purposes, monitoring means and establish the basic requirements for them; from a formal point of view, the decision-making process is considered until the achievement of individual technological tasks. Conclusions: currently, there is a growing interest in the Industry 4.0 concept, in its implementation for the digital transformation of production systems, and one of these areas is the use of IOT technology, which will allow in production conditions to combine elements of flexible integrated production distributed in space, to ensure monitoring of production processes in real time, the functioning of an adaptive control system based on an intelligent decision-making system, which will improve the characteristics of control processes of a robotic system as part of a flexible integrated production.